Design of Village Information Service System Using SMS Gateway - Perwitasari, Ika Devi; Hendrawan, Jodi; Putri, Nadya Andhika (International Conference on Sciences Development and Technology, 2022)
Information is a crucial thing that cannot be separated from everyday life. Kelambir Lima Kebun Village is part of the Hamparan Perak District with a population of 16,355 people. In community life in the village there is a lot of information that sometimes needs to be conveyed by village officials to its citizens. Some examples of this information include the announcement of the COVID-19 vaccination, information on social assistance funds, information on village cooperation, information on the August 17 competition, information on fogging for prevention of DHF, and much other information that exists every day and needs to be conveyed to residents. village. This study aims to create a website information service system website usi3Faculty of Science and Technology, Universitas Pembangunan Panca Budi, Indonesia ng an SMS Gateway. This information service website is used to disseminate information or announcements from the village to villagers via SMS Gateway so that each villager gets the announcement via their respective cell phones. In this way, the accuracy of the information received by residents can be ascertained when compared to when getting information or announcements from neighbors. Researchers used the prototype model for the system development method. In the design, the researcher uses a design tool, namely UML.